Hsa_circ_0008225 inhibits tumorigenesis of glioma via sponging miR-890 and promoting ZMYND11 expression - Xiaoliang Wang; Hongru Feng; Wei Dong; Feng Wang; Gengshen Zhang; Jianliang Wu (Elsevier, 2020)
Background: Circular RNAs (circRNAs) play an important role in the tumorigenesis of glioma. Our study indicated that low hsa_circ_0008225 expression was associated with poor overall survival in patients with glioma. However, the relevant mechanism of hsa_circ_0008225 in glioma tumorigenesis remains unclear. Methods: Two datasets (GSE86202 and GSE92322) were downloaded from the Gene Expression Omnibus (GEO) database. The differentially expressed circRNAs (DEcircRNAs) between glioma tissues and matched normal tissues were screened using R language. Results: A total of 79 overlapping DEcircRNAs were identified by comparison of glioma and matched normal tissues. In addition, low hsa_circ_0008225 expression was associated with poor overall survival in patients with glioma. Overexpression of hsa_circ_0008225 markedly inhibited the proliferation, migration and invasion of SHG44 cells via inducing apoptosis. Mechanically, overexpression of hsa_circ_0008225 increased the expression of miR-890 targeted gene ZMYND11 via acting as a competitive 'sponge' of miR-890. Conclusion: Our results suggested that hsa_circ_0008225 functions as a tumor inhibitor in glioma by sponging miR-890 and then promoting the function of ZMYND11. Therefore, hsa_circ_0008225 could be a potential prognostic biomarker for the treatment of glioma.